Representações sociais dos alunos sobre diferentes espaços de formação em Cursos de Licenciatura em Matemática - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This text presents the results of research, developed in the area of Social Psychology, about the Social Representations of students from Mathematics courses from public institutions of superior education (ISE) in the State of Paraná. This study has attempted to answer the following question: what are the Social Representations of the students of the Mathematics courses, from public ISE in the State of Paraná about the contributions of the different learning environments offered in these courses for their performance as Mathematics teachers in the basic education? Considering such question, it has been defined as the objective of the study: i) to unveil the social representations of the students of public Mathematics courses, concerning the contribution from the different formation environments, offered in these courses in order to act as Mathematics teachers in the basic education. Among the theoretical framework used in this research to cover the questions and objectives proposed, we have emphasized the Social Representation Theory in the dimensional perspective of Serge Moscovici, its precursor, and one of its division, the Central Nucleus Theory, initially conceived by Jean-Claude Abric. As methodological procedures, we have utilized: the application of questionnaires to 200 (two hundred) students from 12 (twelve) public ISE from Paraná, 30 (thirty) interviews with a sample of subjects selected in the 12 (twelve) IES, whose questions were elaborated based on the answers of the questionnaires. The data produced were organized and pre-analyzed using the softwares EVOC, SIMI and ALCESTE. As results, we have obtained as Central Nucleus of the social representations for the contributions: i) from the course – learning, knowledge, mathematics knowledge, and pedagogical knowledge; ii) from the teaching supervised practice – experience, practice, learning, planning, reality, school insertion, didactics, questioning about the profession, reflection; iii) from PIBID – experience, interaction, learning, methodology, practice, opportunity, reflection. These apprehensions of the Central Nucleus reveal the image of the course as a space of the theory, and the image of the teaching supervised practice and PBID as spaces of the practice inside the courses in Mathematics. About the knowledge transmitted in the courses of teachers’ formation, the subjects pointed at the predominance of the mathematical knowledge in relation to the pedagogical contents, considered fundamental to the teaching in the basic education, and their own social representations point at this prevalence. As far as the teaching supervised practice is concerned, this learning environment is taken, predominantly, as a space of practical knowledge acquisition, in a restricted sense, dissociated from the articulation between practice and theory. The PIBID appears as a distinctive opportunity of school insertion, in the sense of time of permanence and type of experience. However, the subjects’ speeches indicate, as well as for the teaching supervised practice, a tendency to consider the school activities at the practical perspective. Finally, it is believed that the social representations of the students of the Mathematics courses about the learning environments analyzed in this study approach the social representations of their teachers, which corroborates the SR theory concerning the role of the context in the production of these representations.
Keywords: Representações sociais; Licenciatura; Formação de professores de matemática; Social representations; Teaching degree; Mathematics teachers’ formation; CNPQ::CIENCIAS HUMANAS::EDUCACAO